Evaluation of knowledge, attitude and practice of dentists about oral health of elderly in 2018 - Katayoun Sargeran; Simin Zahra Mohebbi; Afsaneh Tajik (Tehran University of Medical Sciences, 2021)
Background and Aims: The increase in life expectancy and decrease in birth rate enhances the elderly population in different societies and consequently, the demand from the health system for providing the treatment needs has been elevated. It has been proposed that dentists must improve their attitude, knowledge, and practice to meet these needs. The present study aimed to assess the knowledge, attitude, and practice of general dentists regarding geriatric oral health. Materials and Methods: In this descriptive-analytic cross-sectional study, 150 general dentists participating in the annual congress of the Iranian Dental Association in 2018 were selected and completed a valid and reliable self-administered questionnaire including 5 parts about knowledge, attitude and practice regarding old age and oral health of elders. SPSS23 and multiple regression were used for data analysis. Results: The mean age of dentists was 34.3 (SD: 9.1) and 92 (61.3%) of participants were women. The mean knowledge score about the old age was 16.67 (of maximum: 26, SD: 4.31) and the mean knowledge on the geriatric oral health was 11.01 (of maximum: 18, SD: 2.81). The mean general attitude about elderly was 19.1 (of maximum: 30, SD: 4.26), the mean attitude on geriatric oral health was 13.09 (of maximum: 20, SD: 2.65), and the mean practice about geriatric oral health was 6.5 (of maximum: 10, SD:2.96). Age was significantly associated with knowledge regarding the elderly (P<0.034); i.e. with increase in age lower scores in knowledge were gained. Conclusion: General dentists participating in the congress of the Iranian Dental Association demonstrated a medium level of knowledge, attitude, and practice regarding the oral health of elders. Proper educational programs should be planned in dental schools to improve dental student's knowledge, attitude and practice about geriatric oral health.